Prevalence and prognostic implications of myocardial injury across different waves of COVID-19 - Peiró, Óscar M.; Delgado-Cornejo, Juan R.; Sánchez-Giménez, Raúl; del-Moral-Ronda, Víctor; Lal-Trehan, Nisha; Rocamora-Horrach, Mar; Carrasquer, Anna; Peraire, Joaquim; Fort-Gallifa, Isabel; Bardaji, Alfredo (Frontiers in Cardiovascular Medicine, 2024)
The prognostic ability of myocardial injury across different waves of the COVID-19 pandemic is not well established. The purpose of this study was to evaluate the prevalence and prognostic implications of myocardial injury in the first and sixth wave of COVID-19. We conducted a retrospective observational study that included patients admitted to the emergency department with COVID-19 with data on concentrations of cardiac troponin during the first and sixth wave. We compared the prevalence of myocardial injury and its predictive capacity for 30-day all-cause death in both waves. A total of 346 patients were included (1 st wave 199 and 6 th wave 147 patients). The prevalence of myocardial injury was 21% with non-significant differences between waves. Myocardial injury was associated, in both waves, with a higher prevalence of comorbidities and with an increased risk of 30-day all-cause death (1 st wave HR 3.73 [1.84 -7.55]; p<0.001 and 6 th wave HR 3. 13 [1.23 -7.92]; p=0.016), with non-significant differences in predictive capacity between groups after ROC curve analysis (AUC 1 st wave 0.829 [95% CI 0.764 -0.895] and 6 th wave 0.794 [95% CI 0.711 -0.876]). As limitations, this is a retrospective study with a relatively small simple size and troponin assay was performed at the discretion of the emergency physician so selection bias could be present. In conclusion, the prevalence of myocardial injury and its prognostic capacity was similar in both waves despite vaccination programs. Myocardial injury predicts short-term mortality in all COVID-19 patients, so they should be treated intensively.